PENYULUHAN MANFAAT PEMBERIAN KUNYIT DAN MADU TERHADAP PENURUNAN NYERI HAID (DYSMENORRHAE) PADA REMAJA DI KLINIK CITRA MARENDAL - Mutiara Dwi Yanti (INSTITUT KESEHATAN DELI HUSADA, 2023)
Dysmenorrhea, often known as menstrual pain, is discomfort in the pelvic area caused by menstruation and the release of prostaglandins. In every country, on average more than 50% of women experience dysmenorrhea. Some women experience excruciating pain during menstruation, which can interfere with 50% of the daily activities of women of childbearing age and 85% of the activities of young women. 2020 (Husna, et al). The most common non-pharmacological treatment and often used to relieve menstrual pain or dysmenorrhea in the community is the use of herbal drinks which have efficacy as pain relievers. One of the desirable things to reduce pain without side effects is herbal medicine. Honey is a natural ingredient that is combined with turmeric to make a drink that can reduce menstrual pain. This counseling activity aims to provide enlightenment to the younger generation, especially those in the Marendal environment about the effectiveness of drinking turmeric and honey in relieving adolescent dysmenorrhea. The process of implementing community service is carried out by providing knowledge through counseling and training, especially by educating youth on how to make honey and turmeric drinks and informing them about the benefits and contents of turmeric and honey and distributing pre-test and posttest questionnaires to adolescents. The results obtained were that 83% of 30 adolescents had an increase in adolescent knowledge of how to deal with pain with non-pharmacology, namely by making a drink from turmeric and honey